Building a National Identity Through Dangdut Music Programs on Television (Case Study: D’Academy 5 Indosiar) - Sabagyo, Oktuta Arn; Vera, Nawiroh (Jurnal Komunikasi, 2023)
One of the main functions of television is as a medium of entertainment. Indosiar, one of the private television stations in Indonesia, has an entertainment program called D'Academy 5, which is a talent search program for dangdut musicians and singers. Dangdut music is still considered lower-class music. This music is performed very simply, starting from a makeshift stage, wearing clothes that tend to be sexy, and much more. The mission of the D'Academy 5 program is to raise the image of dangdut music as classy music that can be enjoyed by all levels of society from various social classes. There are even many opinions that say that dangdut music is original Indonesian music, so this music deserves to be called a national identity for Indonesian people. This study aims to see and describe the process of national identity construction carried out by television media through the dangdut music program. This study is qualitative research using the constructivism paradigm. Using the four stages of the social construction theory of mass media: the stage of preparing construction materials, the stage of construction distribution, the stage of forming construction reality, and the stage of confirmation. The case study method is used as an analytical tool. The results of this study indicate that national identity is basically something that must be built and maintained. The identity built through the D'Academy 5 program is not only limited to dangdut music but also includes other cultural elements. There area social values in culture that are maintained and conveyed to the wider community. Indosiar, through this program, tries to emphasize that dangdut is Indonesian music. With the regeneration of dangdut musicians and singers in Indonesia, it is hoped that this music will continue to exist. The elevated image of dangdut music, with audiences from various social classes.